Analysis of SCADA Application on Distribution System Reliability - Marpaung, Noveri Lysbetti; Ervianto, Edy; Amri, Rahyul; Illahi, Hayatul (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2020)
Reliability of Electrical Power Distribution to consumer is strongly influenced by its distribution system. Therefore, electrical power distribution system with high reliability is needed. In distribution of electrical power, reliability level of distribution system is very necessary, because it is influential strongly factor towards continuity of electrical energy distribution to consumers. Parameters can be used to determine reliability level of Electrical Power Distribution System are SAIDI, SAIFI, and CAIDI. SCADA on Electrical Power Ditribution System is needed because it can monitor, control, configure and record working system real time. Besides it, SCADA also can handle interruption temporary or permanently in short time by using remote. Aim of this research is to compare distribution system reliability indexes such as SAIFI, SAIDI and CAIDI before and after integrated with SCADA in Bukittinggi Rayon of PT PLN (Persero), Western Sumatera, Indonesia. This research uses Distribution System Data from 2015 and 2016. Result of this rresearch is Realibility Indexes before Integrated with SCADA(2015) are 15.40 hours/customer, 46.36 interruption/year, 0.33 hour/year, while after Integrated with SCADA(2016) are 2.14 hours/customer, 22.41 interruption/year, 0.10 hour/year. for SAIDI, SAIFI CAIDI Indexes respectivel y. It can be concluded that The increase of Reliability Index after integrated with SCADA are 86.1% for SAIDI, 51.66% for SAIFI, 69.7% for CAIDI.